1995
DOI: 10.1021/bi00016a031
|View full text |Cite
|
Sign up to set email alerts
|

Enzymic and metabolic studies on retrograde regulation mutants of yeast

Abstract: Two nuclear genes, RTG1 and RTG2, which sense the functional state of yeast mitochondria, have been described recently. Yeast strains with null alleles of either of these two genes (delta rtg1, delta rtg2) cannot grow on acetate as the sole carbon source and are auxotrophic for glutamate and aspartate. We report here a series of metabolic experiments and enzyme activity measurements that were made in an attempt to determine the reason for the acetate- phenotype and the glutamate/aspartate auxotrophy. Decreases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 8 publications
2
29
0
Order By: Relevance
“…It has been reported that cells lacking a mitochondrial genome trigger expression of CIT2, which encodes the cytoplasmic citrate synthase, in order to maintain the levels of TCA cycle intermediates to ensure the synthesis of glutamate (19). Deletion of both copies of QCR7 seemed to be sufficient to cause respiratory deficiency but may not have been sufficient to induce retrograde regulation of Cit2p levels (36). Therefore, these results indicate the functional disruption of mitochondria in rip1⌬/rip1⌬ and cyt1⌬/ cyt1⌬ mutants, but not in qcr7⌬/qcr7⌬ deletants.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that cells lacking a mitochondrial genome trigger expression of CIT2, which encodes the cytoplasmic citrate synthase, in order to maintain the levels of TCA cycle intermediates to ensure the synthesis of glutamate (19). Deletion of both copies of QCR7 seemed to be sufficient to cause respiratory deficiency but may not have been sufficient to induce retrograde regulation of Cit2p levels (36). Therefore, these results indicate the functional disruption of mitochondria in rip1⌬/rip1⌬ and cyt1⌬/ cyt1⌬ mutants, but not in qcr7⌬/qcr7⌬ deletants.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial ROS are produced by partial O 2 reduction in the respiratory chain or by damage and loss of membrane potential (76,77). In the last case, the cell uses a retrograde signaling (RTG) from mitochondria to the nucleus to adjust metabolic and biosynthetic pathways and compensate for the loss of mitochondrial quality (78,79). Hog1 activates the RTG pathway in yeast at the transcriptional level (80), but a direct interaction or regulation of mitochondrial proteins by this MAPK has not been reported.…”
Section: Figmentioning
confidence: 99%
“…The best example of such retrograde response is the expression of CIT2 and DLD1, which are induced in response to a mutation that disrupts mitochondrial function and causes a loss of TCA cycle activity or a loss of mitochondrial DNA [49][50] [51]. It could be assumed that lindane treatment inhibits mitochondrial respiration and induces the expression of the nuclear CIT2 gene to facilitate a more efficient utilization of carbon via the transfer of metabolites of glyoxalate cycles (succinate) to TCA cycles [52]. Our data also support recent microarray data on mitochondrial dysfunction that showed the up-regulation of many ORFs that provide support to the cells to overcome the blockage of the TCA cycle in ρ 0 cells [53].…”
Section: Mitochondrial Dysfunctionmentioning
confidence: 99%